Manipulative Speech Techniques in Political Discourse - Finsurovna Shigapova, Farida (2021)
The article is devoted to the analysis of manipulative strategies and tactics in political discourse. The analysis is based on Donald Trump’s speech, which was delivered at the UN General Assembly in 2018. The paper studies the manipulative speech strategies and tactics used by the politician, their characteristic features, linguistic peculiarities of their implementation and the aims of their use. Political discourse defines the necessity to use certain speech strategies and tactics in political speeches, which altogether are aimed at creating an image of a politician and manipulating the consciousness of listeners. Implementation of such strategies and tactics in a proper way can evoke the desired emotional response and have an effect on choices people make. Every politician is unique in using their own strategies and tactics, but, in most cases, such tactics are more or less similar as their target is to create a positive image and make people follow or believe this or that politician.